Sexually Transmitted Diseases Preventive Behavior Among Female Sex Workers - Dwi Retnaningsih; MY Martini; Windyastuti Windyastuti (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Introduction: Sex workers and their customers are the high-risk group population that potentially transmitting sexually transmitted diseases including Human Immunodeficiency Virus (HIV). This research aims to describe the preventive behaviour of female sex workers in preventing transmission of STDs and HIV in Gambilangu Semarang Localization. Methods: This research was qualitative study, The 5 participants of this study were female sex workers who still active in Localization within the period of 2016-2017. Results: The behavior of female sex workers on the prevention of STDs and HIV, were identified as: all participants always offered condoms to clients before sexual transactions, all the participants negotiated the clients to use condom before having sexual intercourse, all participants rejected firmly to have sex with the client suspected having  STDs yet reluctant to use condoms, most participants washed  the vagina using betel soap, consuming herbs and antibiotics without a medical prescription that they believed it could prevent STDs.